2001
DOI: 10.1046/j.1365-2982.2001.00280.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the enterokinetic prucalopride (R093877) on colonic motility in fasted dogs

Abstract: The novel enterokinetic drug prucalopride was tested at various intravenous and oral doses in fasted dogs to assess: (i) the effects on colonic contractile motility patterns; and (ii) the mediation of these effects by 5-hydroxytryptamine (5-HT4) receptors. Colonic motility patterns were assessed in conscious dogs with four chronically implanted strain-gauge force transducers that were sutured on the serosal side of the colon. Prucalopride altered colonic contractile motility patterns in a dose-dependent fashio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
64
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 19 publications
(23 reference statements)
7
64
1
2
Order By: Relevance
“…15 A previous study in dogs demonstrated that prucalopride induces giant migrating contractions in the colon, 16 and it has been demonstrated to accelerate colonic transit both in healthy controls and in patients with chronic constipation, 14,17,18 possibly by mediating an increase in HAPCs, as was observed in healthy volunteers.…”
mentioning
confidence: 99%
“…15 A previous study in dogs demonstrated that prucalopride induces giant migrating contractions in the colon, 16 and it has been demonstrated to accelerate colonic transit both in healthy controls and in patients with chronic constipation, 14,17,18 possibly by mediating an increase in HAPCs, as was observed in healthy volunteers.…”
mentioning
confidence: 99%
“…Prins et al 28 have reported that pD 2 value of cisapride for 5-HT 4 receptors in canine isolated rectum circular smooth muscle is 6.870. 25. 28 Whereas in our study, we found pD 2 values for cisapride and metoclopramide to be 5.55 and 5.40, respectively.…”
mentioning
confidence: 52%
“…This finding was further supported by the lack of effect of GR125487 and GR113808 (potent 5-HT 4 receptor antagonists) on the contraction-response curves to prucalopride in our study. The enterokinetic effects of prucalopride have been reported to be antagonized by GR125487 24,25 and by GR113808. 26 Moreover, our results are in accordance with the finding showing that in human CCP, selective 5-HT 4 antagonist fails to suppress the relaxation caused by 5-HT 4 agonist.…”
mentioning
confidence: 99%
“…25 In the canine colon, prucalopride induced a dose-dependent stimulation of clustered contractile activity in the proximal colon and inhibition in the distal colon. 27 More importantly, prucalopride stimulated giant migratory contractions; the high-amplitude contractions that traverse the length of the colon in an abroad direction and initiate the urge to defecate. 27 The absence, diminution in frequency and/or lower amplitude of these contractions has been linked to the pathophysiology of CC.…”
Section: -Ht4 Receptor Agonists In CCmentioning
confidence: 99%
“…27 More importantly, prucalopride stimulated giant migratory contractions; the high-amplitude contractions that traverse the length of the colon in an abroad direction and initiate the urge to defecate. 27 The absence, diminution in frequency and/or lower amplitude of these contractions has been linked to the pathophysiology of CC. 28,29 Initial studies in healthy human subjects indicated that prucalopride's prokinetic effects were selective for the colon where an acceleration of overall colonic transit and an increase in proximal colon emptying were observed.…”
Section: -Ht4 Receptor Agonists In CCmentioning
confidence: 99%